Benign bone tumors of hand and wrist: evaluation of diagnosis and treatment - GÜRKAN, VOLKAN; Abdallah, Anas; Sofuoglu, Ozden Erhan; Abdallah, Betul Guler; Emel, Erhan; Gunduz, Hasan Burak; Asilturk, Murad (My University, 2020)
Objectives: This study aims to investigate the choke of graft or cement, the relationship between the graft types and union rates, functional results. and complications in hand and wrist benign bone lesions while also evaluating the diagnosis and treatment modalities of lesions with high recurrence potential like giant cell-containing lesions.